The Strategic Role of Brand Image in Linking Celebrity Endorsers and E-Wom with Local Skincare Purchase Intention for People in Jabodetabek - Mayang Nurapriani; Dita Puruwita; Nofriska Krissanya (LPPM Universitas Negeri Jakarta, 2024)
The purpose of this research is to determine the effect of celebrity endorsers and e-wom on the purchase intention of Azarine skincare for people in Jabodetabek through brand image as an intervening. Sample data collection was carried out by distributing questionnaires with Google Forms and using a 5 point Likert scale measurement consisting of strongly agree to strongly disagree. The sampling technique used is a non-probability sampling technique with a purposive sampling method. The research sample used amounted to 250 respondents using a quantitative approach. The data analysis technique uses the Structural Equation Modeling (SEM) method supported by AMOS software version 24. The findings show that celebrity endorsers have a positive and significant effect on brand image. E-WOM has a positive and significant effect on brand image. Additionally, celebrity endorsers have a positive and significant effect on purchase intention. E-WOM has a positive and significant effect on purchase intention. Brand image has a positive and significant effect on purchase intention. Then, celebrity endorser has a positive and significant effect on purchase intention through brand image. E-WOM has a positive and significant effect on purchase intention through brand image.